PERANAN ‘URF DAN ADAT DALAM PEMBENTUKAN HUKUM ISLAM DAN IMPLIKASINYA TERHADAP EKONOMI SYARIAH - Susanty, Widya; Nurhayati, Nurhayati; Anggraini, Tuti (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
The purpose of this study is to analyze the role of 'urf and custom in the formation of Islamic law and its implications for Islamic economics. This study uses a qualitative approach with a library study method to explore the role of 'urf and customary customs in the formation of Islamic law and its impact on Islamic economics. Research data were collected from various literatures, such as books, journals, manuscripts. Document analysis techniques were applied to understand the concept of 'urf and custom from the perspective of Islamic law and its application in the contemporary socio-economic context. The results of the study indicate that Islamic economics, custom ('urf) has a significant role as one of the sources of law that can be used to answer contemporary economic problems. The application of 'urf in Islamic economics can be seen in the activities or transactions of buying and selling salam, bay al wafa' contracts, providing guarantees for the purchase of electronic goods, handover in single currency transactions (taqabuth) and others. Customs help shape local economic practices according to the needs of the community, such as in the buying and selling system, determining marriage dowries, economic cooperation, and distributing zakat and waqf.